EKSPLORASI NILAI-NILAI SOSIAL BUDAYA PADA REMAJA MILLENIAL - Nailul Fauziyah (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2022)
Indonesia has a fundamental norm that is extracted from the noble values of its people. However, the noble values of Indonesian life today have begun to fade due to the influence of foreign cultures and the rapid development of information technology. The purpose of this study was to explore and discover the concept of socio-cultural values among millennial adolescents in the Malang Regency. The method used in this research is a mixed method with a descriptive survey quantitative approach and qualitative grounded theory. This research is in the form of a survey of millennial adolescents in Malang Regency and in-depth data mining on certain respondents. The results of the study show that there are changes and shifts in the understanding of sociocultural values in millennial adolescents such as the concept of the value of tolerance, gotong royong, and courtesy. One of the factors causing the shift in the understanding of these socio-cultural values is gadget technology. The current millennial generation sees the socio-cultural values that exist in society such as (tolerance, gotong-royong, and courtesy) only as a theoretical understanding that they must understand and apply without understanding the substance of the meaning of those values.